2023
DOI: 10.1002/adma.202308241
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Destructive Copper Carriers Induce Pyroptosis and Cuproptosis for Efficient Tumor Immunotherapy Against Dormant and Recurrent Tumors

Luying Qiao,
Guoqing Zhu,
Tengfei Jiang
et al.

Abstract: Activating the strong immune system is a key initiative to counteract dormant tumors and prevent their recurrence. Herein, self‐destructive and multi‐enzymatically active copper‐quinone‐GOx nanoparticles (abbreviated as CQG NPs) have been designed to induce harmonious and balanced pyroptosis and cuproptosis using the “Tai Chi mindset” to awaken the immune response for suppressing dormant and recurrent tumors. One advantage of this cleverly designed material is that it can disrupt the specific antioxidant defen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Most proteins are negatively charged in vivo, and nanocarriers with positive surface charge have a strong adsorption capacity to proteins, which will result in the nanocarriers being easily identified and phagocytosed by cells after entering the body, and then removed from the blood stream, greatly reducing the bioavailability of the drug [36]. The carrier surface design with neutral or negative electric properties can extend the cycle time of the carrier in the body [37,38]. The zeta potential of PdCu@BSA was −11.3 mV, which meant that PdCu@BSA nanomaterials could be stable in the blood circulation (figure 2(e)).…”
Section: Resultsmentioning
confidence: 99%
“…Most proteins are negatively charged in vivo, and nanocarriers with positive surface charge have a strong adsorption capacity to proteins, which will result in the nanocarriers being easily identified and phagocytosed by cells after entering the body, and then removed from the blood stream, greatly reducing the bioavailability of the drug [36]. The carrier surface design with neutral or negative electric properties can extend the cycle time of the carrier in the body [37,38]. The zeta potential of PdCu@BSA was −11.3 mV, which meant that PdCu@BSA nanomaterials could be stable in the blood circulation (figure 2(e)).…”
Section: Resultsmentioning
confidence: 99%
“…Rhodamine B (RhB) was loaded in Bi-Bi 2 O 3−x S x to make Bi-Bi 2 O 3−x S x qualify the ability of cell fluorescence imaging [30]. Typically, RhB and Bi-Bi 2 O 3−x S x were stirred for 24 h in dimethyl sulfoxide at a ratio of 1 : 1 in the dark.…”
Section: Cell Uptakementioning
confidence: 99%
“…These drugs have demonstrated efficacy in inhibiting tumor growth, leading to noticeable histopathological damage, and eliciting a strong immune response with minimal systemic toxicity. [28][29][30][31] Bioinformatics studies have also found that tumor cells with distinct cuproptotic characteristics exhibit varying levels of sensitivity to targeted therapies and immunotherapy. The intricate mechanisms underlying cuproptosis across various tumor types indicate that it has potential as a therapeutic avenue for urological tumors.…”
Section: Introductionmentioning
confidence: 99%